Tissue Factor Induces Migration of Cultured Aortic Smooth Muscle Cells - Sato, Yuichiro; Asada, Yujiro; Marutsuka, Kousuke; Hatakeyama, Kinta; Sumiyoshi, Akinobu (Thrombosis and Haemostasis, 1996)
Tissue factor (TF) plays a key role as a primary initiator on the extrinsic coagulation cascade. Recently, upregulation of TF has been reported in human atherosclerotic lesions. We investigated the effects of TF on migration and proliferation of cultured smooth muscle cells (SMCs) from rabbit aortas. We tested three kinds of recombinant human TF (L-TF: the full length of TF with relipidation, NL-TF: the full length of TF without relipidation, and S-TF: a soluble form of TF1-219). Only L-TF had coagulant activity. All kinds of TF showed the chemotactic migration activity for SMCs. The migration ability of TFs was comparable to those of platelet-derived growth factor (PDGF)-BB and basic fibroblast-growth factor (bFGF), and was inhibited by anti-TF polyclonal and monoclonal antibodies. On the other hand, none of the forms of TF induced SMC proliferation. These results indicate that TF is not only a coagulation factor but also a strong chemotactic factor for vascular SMCs, and suggest that TF could play an important role in atherogenesis as well as in hemostasis and thrombosis.